Mining Cryptocurrency di Blockchain - Indika Rakhman; Munir Munir; Nurul Musyafa’ah; Sri Minarti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Mining cryptocurrencies on the blockchain is a method for collecting crypto by breaking secret codes compiled with mathematical algorithm equations. Miners will receive rewards in the form of digital coins according to the amount of crypto mined and the type of crypto, this is because each crypto has its own level of difficulty. Crypto includes electronic money (e-money), where the use of e-money as a medium of exchange in modern transactions is still being debated among contemporary scholars about its legitimacy. Two things that become the problem are (1) what is the mechanism for mining cryptocurrency on the blockchain, (2) how is the review of Islamic Economic Law on cryptocurrency mining on the blockchain. The purpose of this study is to describe and explain cryptocurrency mining practices on the blockchain and to find out the review of Islamic Economic Law on cryptocurrency mining. This research is a qualitative research by collecting data and information through interviews. The data sources include primary data sources, namely interviews with crypto miners, secondary data sources, namely books, journals, theses, scientific papers and other written works. While the tertiary data comes from dictionaries, encyclopedias, and related articles. This research data collection method obtained from interviews, observation, and documentation. While the method used to analyze the data is a qualitative analysis method using the theory of mining, al-mal, and ju'alah. From the research results it is known: (1) The cryptocurrency mining mechanism on the blockchain is carried out with a supercomputer facilitated by a GPU, FPGA or ASIC by using certain scripts on the BTC/ETH network to find new blocks containing crypto to get rewards (sell). (2) According to the Sharia Economic Law review of mining cryptocurrency on the blockchain, crypto reward (ju'al) results can be accepted as assets according to the definition of the Hanafiyyah scholars, Ibn Abidin, Imam az-Zaila'i, Imam al-Syatibi, Ibn Arabi and Syafii scholars. However, it is not accepted as a means of payment like conventional money (gharar, dharar, qimar), but both must comply with the conditions and limits set by the Shari'a, this is stated in the Fatwa of the National Sharia Council-Indonesian Ulema Council No: 116/DSN-MUI/ IX/2017 concerning Sharia Electronic Money.